ANALISIS PENGAWASAN NETRALITAS APARATUR SIPIL NEGARA (ASN) OLEH BADAN PENGAWAS PEMILIHAN UMUM (BAWASLU) PROVINSI JAWA TENGAH PADA PEMILU TAHUN 2024 - Istikomah, Siti -; -, Yuwanto -; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2024)
This study analyzes the supervision process carried out by the General Election Supervisory Agency (Bawaslu) regarding the neutrality of the State Civil Apparatus (ASN) in the 2024 Election. The aim is to address violations of ASN neutrality, which remain a complex issue that has persisted through the 2024 Election Event. ASNs are expected to refrain from taking sides or showing favoritism towards any candidate. The study utilizes Donelly et al.'s supervision theory (in Zuhad, 1996: 302), which encompasses Pre-eliminary Control, Current Control (Supervision at the Election Implementation Stage), and Feedback (Post-Voting Supervision). This research adopts a qualitative approach with data collection techniques including interviews and literature studies. The findings of this study reveal that the supervision process regarding the neutrality of the State Civil Apparatus (ASN) in the 2024 Election, carried out by the General Election Supervisory Agency (Bawaslu), has been largely effective. This is evidenced by the monitoring of 46 instances of ASN neutrality violations by forwarding to KASN for the imposition of. Firstly, in supervising the preparation for the 2024 Election, Bawaslu Central Java has taken a series of preventive measures to avert violations of ASN neutrality. These include socialization efforts, establishment of supervision standards in accordance with laws and regulations governing ASN neutrality, collaboration with various stakeholders for supervision, and provision of adequate budget. Monitoring the implementation of the 2024 Election stages, Bawaslu has developed procedures and processes for reporting on ASN neutrality, both through direct office visits and online submissions via Sigap Laporprovided training, debriefing, and technical guidance to enhance the supervisory capabilities of all collaborating stakeholders; oversees the monitoring of violations of ASN neutrality both directly and indirectly; repressive action to follow up on violations. Post-voting supervision is conducted to assess effectiveness, quality, and identify any shortcomings that require evaluation. For instance, issues such as inadequate budget resources causing interruptions in the online reporting system through Sigap Lapor, limited human resources to process large volumes of data, and lack of supervision leading to ASNs being affiliated with political parties are highlighted